Validation of a name of a northern Sumatra endemic Begonia antoi (Begoniaceae) - Rezeki, Juli T.s.; Arico, Zulfan; Mustaqim, Wendy A.; Girmansyah, Deden; Ardi, Wisnu H.; Hughes, Mark (Phytotaxa, 2026)
N/A